Rapid mixing with high‐throughput in a semi‐active semi‐passive micromixer. Issue 9 (29th March 2017) - Kunti, Golak; Bhattacharya, Anandaroop; Chakraborty, Suman
Abstract : In this paper, we investigate a novel alternating current electrothermal (ACET) micromixer driven by a high efficiency ACET micropump. The micromixer consists of thin film asymmetric pairs of electrodes on the microgrooved channel floor and array of electrode pairs fabricated on the top wall. By connecting electrodes with AC voltage, ACET forces are induced. Asymmetric microgrooved electrodes force the fluids along the channel, while lateral vortex pairs are generated by symmetric electrode pairs located on the top wall. Waviness of the floor increases contact area between two confluent streams within a narrow confinement. An active mixer operates as a semi active semi passive mixer. Effects of various parameters are investigated in details in order to arrive at an optimal configuration that provides for efficient mixing as well as appreciable transport. It is found that using a specific design, uniform and homogeneous mixing quality with mixing efficiency of 97.25% and flow rate of 1.794 μ m 2 / min per unit width of the channel can be achieved.